2019
DOI: 10.3390/ijms20051144
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory FK506 and Minocycline Treatment Alleviates Prion-Induced Neurodegenerative Events via Caspase-Mediated MAPK-NRF2 Pathway

Abstract: Transcription factors play a significant role during the symptomatic onset and progression of prion diseases. We previously showed the immunomodulatory and nuclear factor of activated T cells’ (NFAT) suppressive effects of an immunosuppressant, FK506, in the symptomatic stage and an antibiotic, minocycline, in the pre-symptomatic stage of prion infection in hamsters. Here we used for the first time, a combinatory FK506+minocycline treatment to test its transcriptional modulating effects in the symptomatic stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Besides, NF-κB could also increase the survival ability in endothelial cells and cardiomyocytes under LPS stimulation [23]. Previous study also indicated that the translation of NF-κB could be activated by rutin treatment via increasing the phosphorylation of p38-MAPK signaling pathway [24,25]. NO in endothelial cells were synthesized by eNOS, and the expression and activity of eNOS is largely related to the function of endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, NF-κB could also increase the survival ability in endothelial cells and cardiomyocytes under LPS stimulation [23]. Previous study also indicated that the translation of NF-κB could be activated by rutin treatment via increasing the phosphorylation of p38-MAPK signaling pathway [24,25]. NO in endothelial cells were synthesized by eNOS, and the expression and activity of eNOS is largely related to the function of endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…The octadecyl chain can attach to and remain on activated macrophage/microglial cell membranes for a long time, while the short peptide sequence can be specifically cleaved by MMP9 for responsive and controlled drug release. [37,38] Because short peptides have free amino groups and GOQDs have many carboxyl groups on their surfaces, covalent coupling of C18P to GOQDs via amide bonds can be achieved using EDC/NHS chemical crosslinking methods.…”
Section: Methodsmentioning
confidence: 99%
“…[ 34,35 ] However, there is a concern that GOQDs are readily susceptible to becoming metabolized in the eye and lack selectivity for specific cell types. [ 36 ] Minocycline (MC) is a potent MMP9 and macrophage/microglia activation inhibitor with well‐defined anti‐inflammatory properties [ 37 ] and is considered a good candidate to prevent inflammation and dampen degenerative processes in the retina. [ 38 ] Minocycline is generally well‐tolerated and has been in clinical trials for retinal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, the expression of the apoptotic marker caspase 3 markedly increased (Figure 4B). It was reported previously that the FK506 binding proteinmediated MAPK pathway can alleviate prion-induced neurodegeneration [12]. The role of the MAPK pathway regulated by FKBP52 in polycystic ovary syndrome (PCOS) has also been reported [13].…”
Section: Fkbp11 Significantly Increases the Apoptosis Rate In Osteosa...mentioning
confidence: 97%